2017
DOI: 10.1155/2017/9706493
|View full text |Cite
|
Sign up to set email alerts
|

Active Control for Multinode Unbalanced Vibration of Flexible Spindle Rotor System with Active Magnetic Bearing

Abstract: The unbalanced vibration of the spindle rotor system in high-speed cutting processes not only seriously affects the surface quality of the machined products, but also greatly reduces the service life of the electric spindle. However, since the unbalanced vibration is often distributed on different node positions, the multinode unbalanced vibration greatly exacerbates the difficulty of vibration control. Based on the traditional influence coefficient method for controlling the vibration of a flexible rotor, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…On the basis of a 19.4% increase in balance capacity, thickness dropped from 38 mm to 28 mm, a drop of 26.3%. e volume of balanced terminal dropped from 160549 mm 3 to 83780 mm 3 with 47.8% drop ratio. e mass of balanced terminal has dropped from 562 g to 387 g with a drop ratio of 31.1%, so that the additional mass added by the balanced terminal to the spindle will be effectively reduced.…”
Section: New Integrated Balancementioning
confidence: 98%
See 2 more Smart Citations
“…On the basis of a 19.4% increase in balance capacity, thickness dropped from 38 mm to 28 mm, a drop of 26.3%. e volume of balanced terminal dropped from 160549 mm 3 to 83780 mm 3 with 47.8% drop ratio. e mass of balanced terminal has dropped from 562 g to 387 g with a drop ratio of 31.1%, so that the additional mass added by the balanced terminal to the spindle will be effectively reduced.…”
Section: New Integrated Balancementioning
confidence: 98%
“…So, balancing the liquid in the terminal chamber will stress the chamber due to centrifugal force. Assuming the rotational speed is 30000 rpm, the cavity of the balance terminal is filled with the weight fluid with density 0.8 g/mm 3 , and the centrifugal force produced by the weight fluid in a single cavity can be calculated by the following equation:…”
Section: New Integrated Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al, (2018) found that coupling had a greater impact on dynamic bearing forces through substructure methods and generalized finite element methods [23]. Aiming at the unbalanced vibration problem of the spindle drum device during high-speed cutting, Qiao et al, (2017) proposed a method for controlling the optimal influence coefficient of multi-node unbalanced vibration of flexible electric spindle [24]. Liu et al, (2019) proposed an innovative dynamic model for vibration analysis of flexible drum bearings [25].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional mechanical bearings, magnetic bearings utilize magnetic forces to support a shaft without any physical contact. It offers advantages of no friction, no lubrication, and long lifespan [1][2][3][4][5]. One of the most promising features of magnetic bearings is that the dynamic performance of the shaft is able to be shaped to different applications.…”
Section: Introductionmentioning
confidence: 99%